Novel Functional Risk Factors for the Prediction of Cardiovascular Events in Vulnerable Patients Following Acute Coronary Syndrome - Reriani, Martin K (2012)
Over the years there has been considerable improvement in the clinical outcomes of patients treated for acute coronary syndrome (ACS). Despite a significant reduction in acute mortality, a large percentage of patients post ACS continue to experience adverse cardiovascular (CV) events, with high long-term mortality rates and overall suboptimal medical management. Long-term risk prediction tools rely on traditional CV risk factors and are developed and validated in specific populations. Established CV risk factors, however, only explain half or fewer of CV events. These risk models may thus not be optimal in determining individual risk for long-term adverse outcomes or in helping to identify individual patients who do not respond to therapy. Identifying the specific plaque characteristics associated with increased likelihood for thrombotic complications and rapid progression has led to the concept of the vulnerable plaque. Recently, “vulnerable myocardium” (ie, myocardium that is prone to myocardial ischemia and fatal arrhythmia) has been shown to play an important role in outcome. Both vulnerable plaque and vulnerable myocardium are associated with functional vascular abnormalities, such as endothelial dysfunction, which are considered a key event in the initiation, progression and complications of coronary artery disease. Endothelial dysfunction may serve as an underlying unifying mechanism that would independently predict long-term outcome in patients with ACS undergoing revascularization.